Analysis Of Selenium Species Using Cathodic Stripping Voltammetry (Jurnal Teknologi (Sciences & Engineering), 2012)
M respectively when an accumulation potential of 100 mV was applied for 90 seconds. Simultaneous determination of selenite and dimethyl diselenide was also carried out. The effect of selenite on the determination of dimethyl diselenide and vice versa was studied. The influence of metal ions such as lead, copper, cadmium and zinc on the reduction signals for selenite and dimethyl diselenide was also investigated. Key words: Cathodic stripping voltammetry, Se(IV), dimethyldiselenide